Réponses

2013-10-12T18:51:42+02:00
Bonjour
f(x) = (3x-5)² -4x² 
1) factoriser
f(x) = (3x-5)² - (2x)² 
f(x) = (3x-5-2x)(3x-5+2x)
f(x) = ( x -5)( 5x-5) 
developper
f(x) = 5x² - 5x - 25x +25 
f(x) = 5x²-30x +25 
2013-10-12T18:57:20+02:00
1) On utilise une identité remarquable : (a + b)(a - b) = a² - b²
f(x) = (3x - 5)² - 4x²
f(x) = (3x - 5 - 2x)(3x - 5 + 2x)
f(x) = (x - 5)(5x - 5)

2) On utilise la double distributivité : (a -b)(c -d)
f(x) = (x - 5)(5x - 5)
f(x) = 5x² - 5x - 25x + 25
f(x) = 5x² - 30x + 25